Pengaruh Perceived Usefulness dan Perceived Ease Of Use terhadap Repurchase Intention pada Pengguna Aplikasi Traveloka - Aldiyanda Ramadhana; Abdul Rahman Lubis (Manajemen Inovasi Bisnis dan Strategi, 2023)
This study aims to determine the effect of Perceived Usefulness and Perceived Ease of use on Repurchase Intention through Trust and User Satisfaction for Traveloka user in Banda Aceh City. Data were collected through a survey of 210 respondents as sample to represents the research population and used a questionnaire as the data collection instrument. The sample technique used is non-probability sampling with purposive sampling technique. Statistical product and service solutions (SPSS) are used as an analytical method to determine the effect of the variables involved. The results of the study show that Perceived Usefulness and Perceived Ease of use have a positive effect on User Satisfaction and Trust. Perceived usefulness and Perceived ease of use have a positive effect on Repurchase Intention. Trust and User Satisfaction has a positive influence on Repurchase Intention. Perceived Usefulness and Perceived Ease of use have a positive effect on Repurchase Intention when mediated by User Satisfaction and Trust.Keyword: Perceived Usefulness, Perceived Ease of Use, User Satisfaction, Trust, Repurchase Intention